Behavioral report of Chrysomya rufifacies in response to substrate infestation by Lucilia sericata and Lucilia cuprina using a tetrahedron olfactometer device - Fonseca-Muñoz, Alicia; Hernández-Salinas, Gregorio; Ordaz-Silva, Salvador; López-Sánchez, Imelda Virginia; Delgadillo-Ángeles, Jorge Luis; Villanueva-Sánchez, Evert; Villanueva-Verduzco, Clemente; Gómez-Domínguez, Nadia S.; Granados-Echegoyen, Carlos (Frontiers in Insect Science, 2024)
Calliphoridae are widespread globally and can inhabit a variety of habitats. In this brief report, we assessed the appeal of Chrysomya rufifacies to resources that were previously inhabited by Lucilia sericata and L. cuprina, both common carrion colonizers. Two hundred adult male and female (1:1) C. rufifacies were released under controlled conditions into clear plastic cages (45 x 45 x 45 cm) with four types of substrates: beef-liver; liver with 100 third-instar larvae of L. cuprina; (III) liver containing 100 third-instar larvae of L. sericata; and liver containing 100 third-instar larvae of C. rufifacies. Each substrate was left in place for 24 hours at the end of a tube connected to the cage, where sticky traps were positioned to capture flies that might have been attracted to a specific substrate. The results indicate variations in the attraction of flies to different types of livers colonized by larvae of various species. It is suggested that flies may have specific preferences depending on the species of larvae present in the substrate. The liver without larvae was the preferred choice, while beef liver with C. rufifacies larvae was the least attractive. Results of statistical tests indicated that there is independence between attractiveness preference and the presence of C. rufifacies flies. Although there is a trend among certain levels of the variables in the correspondence analysis, these relationships are not statistically significant. However, they indicate specific patterns of association between different groups of flies and species of larvae. This study demonstrated that C. rufifacies does not show reduced attraction to any of the resources. A tetrahedron olfactometer device has been used for the first time in a behavioral study of C. rufifacies flies. This may enable future studies to enhance the understanding of fly behavior.